Faktor Pendukung dan Penghambat Dalam Pemberian Bantuan Fish Finder Oleh Dinas Pertanian, Pangan dan Perikanan Kota Pariaman Bagi Nelayan di Kota Pariaman - Naya Dwi Wahyuni; Fitri Eriyanti (Penerbit Jurnal Indonesia, 2024)
This research aims to explain the supporting and inhibiting factors in providing fish finder assistance to fishermen in Pariaman City. This research is qualitative research with a descriptive approach. The research was conducted in Pariaman City, West Sumatra Province. The data in this research was obtained from interviews, observations and documentation studies. Testing the validity of the data in this research is using source triangulation techniques and method triangulation techniques. Based on the results of the research and discussion, it was found that the supporting factors and inhibiting factors in providing fish finder assistance by the Department of Agriculture, Food and Fisheries of Pariaman City for fishermen in Pariaman City were the supporting factors in providing fish finder assistance for fishermen in Pariaman City was the commitment of the service that provided and The need for fish finding assistance for fishermen. The inhibiting factor in providing fish finder assistance in Pariaman City lies in the absence of socialization of the fish finder assistance program. Then there is no training and assistance regarding how to use fish finders for fishermen in Pariaman City.